(untitled) (Psychology Travelogs, 2023)
The article highlights the main tasks of psychological and pedagogical influence on young people in order to reduce the level of emotional disorders. It has been established that socio-legal, socio-household, socio-medical, psychological and pedagogical, socio-economic, socio-psychological factors have a systemic impact on the development of emotional disorders in youth. The need to adapt the approach to the organization of psychological and pedagogical interaction with young people is highlighted. The purpose of the article is to theoretically substantiate the need to create a model of structural and functional psychological and pedagogical influence on youth with emotional personality disorders. To achieve this goal, a number of tasks have been identified: to theoretically study and summarize the leading scientific experience on the peculiarities of an integrated approach to the formation of socially identical youth. The study was conducted using the methods of theoretical, empirical research and general methods of scientific research. The novelty of the study is to plan a model of integrated interaction of teachers in order to minimize the impact of emotionally unstable disorders of young people, to create an integrated approach to restore the psycho-emotional well-being of youth education students. A review of statistical and analytical data has led to conclusions about the need to develop new competencies among young people in order to reduce the level of emotional instability. The deterioration in the mental well-being of young people requires cooperation to enhance the effectiveness of all elements of social interaction. Comparative data analysis and case study report allowed us to structure the most typical causes of dysfunctions, the main signs that educators should pay attention to in their daily work. The conclusions summarize the consideration of the necessary pedagogical aspects of an individual’s interaction in society.